From tissue retrieval to electron tomography: nanoscale characterization of the interface between bone and bioactive glass - Micheletti, Chiara; Gomes-Ferreira, Pedro Henrique Silva [UNESP]; Casagrande, Travis; Lisboa-Filho, Paulo Noronha [UNESP]; Okamoto, Roberta [UNESP]; Grandfield, Kathryn (The Royal Society, 2021)
The success of biomaterials for bone regeneration relies on many factors, among which osseointegration plays a key role. Biogran (BG) is a bioactive glass commonly employed as a bone graft in dental procedures. Despite its use in clinical practice, the capability of BG to promote osseointegration has never been resolved at the nanoscale. In this paper, we present the workflow for characterizing the interface between newly formed bone and BG in a preclinical rat model. Areas of bone-BG contact were first identified by backscattered electron imaging in a scanning electron microscope. A focused ion beam in situ lift-out protocol was employed to prepare ultrathin samples for transmission electron microscopy analysis. The bone-BG gradual interface, i.e. the biointerphase, was visualized at the nanoscale with unprecedented resolution thanks to scanning transmission electron microscopy. Finally, we present a method to view the bone-BG interface in three dimensions using electron tomography.
Keywords: Biogran; biointerphase; electron tomography; focused ion beam; osseointegration; scanning transmission electron microscopy